2021
DOI: 10.3389/fpsyg.2021.741821
|View full text |Cite
|
Sign up to set email alerts
|

Self-Handicapping in Chinese Medical Students During the COVID-19 Pandemic: The Role of Academic Anxiety, Procrastination and Hardiness

Abstract: Background: In the face of the 2019 Coronavirus Disease (COVID-19) outbreak, Chinese medical students worried about their future studies which might make them more susceptible to academic anxiety. Previous studies have shown that academic anxiety is an important risk factor for self-handicapping, but there are few studies to explore the relationship between the two which may be mediated or moderated by other variables. Therefore, this study investigated how Chinese medical students' academic anxiety is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 73 publications
(73 reference statements)
0
13
0
1
Order By: Relevance
“…Pekrun pointed out that academic emotions encompass all emotional experiences that a person may experience during the life course ( 44 ). Medical undergraduates are already under high academic and social pressure, which can cause procrastination ( 32 ). Major events, such as the COVID-19 pandemic, might trigger learning anxiety, boredom in association with homework, loss of interest in learning or no expectation of success in examinations, or even professional identity and professionalism among medical undergraduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pekrun pointed out that academic emotions encompass all emotional experiences that a person may experience during the life course ( 44 ). Medical undergraduates are already under high academic and social pressure, which can cause procrastination ( 32 ). Major events, such as the COVID-19 pandemic, might trigger learning anxiety, boredom in association with homework, loss of interest in learning or no expectation of success in examinations, or even professional identity and professionalism among medical undergraduates.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding medical professionals and undergraduates, similar to the burnout phenomenon mentioned above, procrastination, i.e., the needless delay of things that one intends to do, is also a major risk factor for low well-being ( 31 ). Evidence suggests that procrastination is positively correlated with academic anxiety ( 32 ), distress ( 33 ) and low motivation in students ( 34 ), resulting in more agitation before a test or poor academic performance across the entire semester. Besides the psychological aspects, a correlation between procrastination and the academic environment has also been demonstrated among medical students ( 35 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, [40] showed that self-handicapped students were more likely to be maladaptive perfectionists than non-self-handicapped students. [41] argues that the relationship between academic anxiety and self-handicapping of students was moderated by hardiness. Moreover, [5] showed that academic buoyancy was associated with higher levels of academic achievement as well as controlled and autonomous motivational orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Dukungan sosial merupakan bagian dari jaringan komunikasi timbal balik dari orang tua, kekasih, kerabat, teman, lingkungan sosial dan masyarakat. Saat seseorang didukung oleh lingkungan sosialnya maka segalanya akan terasa lebih mudah dan individu itu merasa diperhatikan dan dipedulikan sehingga menimbulkan rasa percaya diri (Jia, 2021). Fauziah, (2016) menyatakan bahwa dukungan sosial memang sangat mempengaruhi prokrastinasi akademik, apabila dukungan sosialnya tinggi maka tingkat prokrastinasi akademik cenderung akan rendah, begitu pula sebaliknya apabila dukungan sosial rendah maka tingkat prokrastinasi akademik cenderung akan tinggi.…”
Section: Pendahuluanunclassified